Pengaruh Fashion Lifestyle, Sosial Media Marketing, Dan Variasi Produk Terhadap Minat Beli Produk Thrift Di Kota Malang (Studi Kasus Pada Gen Z Di Kecamatan Lowokwaru) - Aditya Wahyudin Harun; Rois Arifin; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to examine the influence of fashion lifestyle, social media marketing, and product variation on Generation Z’s purchase intention toward thrift products. A quantitative approach with a survey method was employed, involving 129 respondents selected through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 31. The results indicate that all variables simultaneously have a positive and significant effect on purchase intention. Partially, fashion lifestyle, social media marketing, and product variation each show a positive and significant influence on purchase intention. These findings suggest that alignment with fashion lifestyle trends, effective social media marketing, and diverse product offerings play an important role in enhancing Generation Z’s purchase intention toward thrift products. This study emphasizes the importance of implementing an integrated marketing strategy to attract young consumers in the sustainable fashion industry. Keywords: Fashion Lifestyle, Social Media Marketing, Product Variation, Purchase Intention.